(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
Complexation of remote and first of all of aerospace and hydrogeophysical methods is an important methodical aspect aimed on establishment of formation and distribution of regularities of an underground runoff in the studied region. It is an establishment of tectonic structures, a relief of regional confining layer, lithology and water-physical properties of rocks. In the work specified questions are discussed on the example of massif Aragats (as a typical volcanic region).